The handbook of food and anthropology - Klein, Jakob (Bloomsbury Academic, 2019)
This Handbook features 20 original essays by leading figures in the discipline, which examine traditional areas of research as well as cutting-edge areas of inquiry. Divided into three parts – Food, Self and Other; Food Security, Nutrition and Food Safety; Food as Craft, Industry and Ethics – the book covers topics such as identity, commensality, locality, migration, ethical consumption, artisanal foods and children's food. Each chapter features rich ethnography alongside wider analysis of the subject. Internationally renowned scholars offer insights into their core areas of specialty including Michael Herzfeld on culinary stereotypes, David Sutton on how to conduct an anthropology of cooking, Johan Pottier on food insecurity and Melissa L. Caldwell on practising food anthropology.--Provided by publisher.